The 21st Century Competency Development of Staff’s Rajabhat University in Lower Northern Group - Noyaime , Nathaphon; Kosonkittiumporn , Saovalak (Journal for Developing the Social and Community, 2023)
This research is mixed methods research which has research objectives to (1) study the factors affecting the development of competency of support university staff in the 21 st century of Rajabhat Universities in the lower northern region. (2) Create a model for developing the competency of support university staff in the 21st century of the lower northern group of Rajabhat Universities. (3) Confirm the model for the development of competency development of university staff in the 21st century of Rajabhat University in the lower northern group. The 3 phases of research are as follows: Phase 1 is quantitative research to study the factors affecting the development of competency of support university staff in the 21st century of Rajabhat University in the lower northern region. The second phase is qualitative research to create a model for developing the competency of supporting university staff in the 21st century of Rajabhat University groups in the lower northern region. Phase 3 is quantitative research to confirm the model of the 21 st-century supportive university staff competency development of universities. Rajabhat group in the lower northern region. The samples used in the research were divided into 3 groups as follows: Group 1: Supporting University Employees of Rajabhat University, Lower Northern Group consisting of University Employees of Phetchabun Rajabhat University, Pibulsongkram Rajabhat University, Nakhon Sawan Rajabhat University, University. Kamphaeng Phet Rajabhat, and Uttaradit Rajabhat University 400 people. The sample size was determined using a threshold of not less than 20 times the variable. Data collection tools are questionnaires. The second group of samples was 17 participants who were involved and involved in providing key information to the Focus Group Discussion, using purposive sampling. The tools used are structured interviews. The third group of samples was experts in confirming the suitability of the 21st-century supportive university staff competency development model of 5 lower northern groups of Rajabhat Universities, using purposive sampling. Quantitative Analysis with Basic Static, Structural Equation Model. Confirmation of the 21st Century Supporting University Staff Competency Development Model of Rajabhat Universities in the Lower Northern Group by Method Connoisseurship with tools as Questionnaire. The results showed that (1) factors affecting the competency of the staff of supporting universities in the 21st century of Rajabhat Universities in the lower northern group with statistical significance at the .05 level were; Strategic Leadership, Performance Indicator Management, and Organization Learning. These three factors could account for the variation in the 21st-century supportive university staff performance of the lower northern group of Rajabhat Universities with an accuracy of 75.30 percent (R2 = 0.753), and the model is consistent with the empirical data (x2 = 147.689, df = 88, x^2/df=1.678, CFI = 0.984, TLI = 0.978, RMSEA = 0.041, SRMR = 0.033). (2) A model for developing the competency of supporting university staff in the 21st century of Rajabhat University in the lower northern region, which can be created as an activity project that promotes Strategic Leadership, Performance Indicator Management, and Organization Learning for university staff in the support line of the university. Rajabhat group in the lower north has a total of 5 main projects, 11 sub-activities such activity projects lead to the creation of a model for the development of university staff performance in the 21st century of the lower northern group of Rajabhat Universities, and (3) Confirmation of the suitability of the 21st-century supportive university staff competency development model of the lower northern Rajabhat University was found to be at the highest level and the quartile consistency was less than 1.5 in all approaches, thus showing high consistency. Expert recommendations include; (3.1) The workload of the university support staff should have a mission to assist academic personnel in performing their duties in research repository for local development. (3.2) Conducting institutional research of supporting university staff The focus should be on the use of innovation to improve operational methods and mechanisms in the roadmap. (3.3) The results of the work for ascent into the professional and specialized position should have institutional research results for consideration, And (3.4) Activities to promote and develop leadership should include activities to promote morality and professional ethics. activities freely. Should encourage students to exchange learning between groups or faculty. Should organize more analytical activities in teaching and learning and support the use of technologies such as Line and Facebook.